An Application of the Social Cognitive Career Theory Model of Career Self-Management to College Athletes’ Career Planning for Life After Sport - Wendling, Elodie; Sagas, Michael (Frontiers in Psychology, 2020)
Drawing on Lent and Brown’s (2013) recently developed Social Cognitive Career Theory (SCCT) model of Career Self-Management (CSM), we aimed to determine the key predictors and underlying theoretical mechanisms of college athletes’ career planning processes for life after sport. Ten variables were operationalized (i.e., career planning for life after sport, career decision self-efficacy, career goals, perceived career planning support from coaches, perceived career planning barriers, conscientiousness, openness, extraversion, neuroticism, and agreeableness) to assess the hypothesized CSM model. A survey design was utilized on a sample of 538 NCAA Division I college athletes in the United States to test the model. The measurement and hypothesized models were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The measurement model demonstrated satisfactory reliability and validity for all measures. Several significant direct, indirect, and moderating relationships of the cognitive, contextual, and personality variables on career planning were observed. The CSM model was found to be a useful theoretical framework that explained 62.7% of the variance on career planning. The model, along with the validated measures that support it, can help both researchers and practitioners to leverage facilitating (i.e., self-efficacy, career goals, conscientiousness, openness, and extraversion) and impeding (i.e., career barriers) factors of the career planning processes in their work.